The Gospel of Mark within Judaism: Reading the Second Gospel in Its Ethnic Landscape - Van Maaren, John (My University, 2019)
This thesis argues that the Gospel of Mark reflects a social location within the social boundaries of the Jewish ethnos and outlines relevant features of Mark’s configuration of Jewishness. It is divided into two parts. Part one provides a flexible definition of Jewishness in antiquity in order to assess what it meant to be Jewish and what characterized the boundaries between Jews and non-Jews. It makes an independent contribution to the study of Jewishness in antiquity by using a recent sociological model that explains how and why ethnicity matters in certain societies and contexts to map changes and features of Jewishness during the Hasmonean and Early Roman periods (129 BCE–132 CE) in the Southern Levant. It also addresses the relevant methodological issues for locating texts in relation to a social category such as “Jewish.” Part two addresses the Gospel of Mark through the same methodological lens and in light of the re-conceptualization of Jewishness. It both argues that Mark should be read as a Jewish text and addresses how Mark configures Jewishness. It shows that the categorical boundaries in the text reflect a common Jewish way of categorizing and ranking people. In particular, Mark’s narrative assumes a hierarchical relation between the Jews and other people groups (i.e., “gentiles” or “the nations”) in which Jews are to the nations as children are to dogs. In addition, Mark’s narrative employs the concept of the kingdom of God to remake the boundary system of Roman Judea in two ways. First, Mark attempts to overturn the hierarchical Roman/Jew boundary by presenting the kingdom of God as imminent, earthly, and entailing the end of Roman power. Second, Mark subdivides the Jewish ethnos by limiting kingdom membership to “righteous” members of the Jewish ethnos, a strategy shared with the majority of Jewish texts examined in part one. The concluding section addresses the configuration of Jewishness in Mark’s narrative in terms of six common features of ethnic identity.
Keywords: Gospel of Mark; Ethnicity; Judaism